2019
DOI: 10.1136/vr.105540
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the process and decision‐making around companion animal euthanasia on veterinary wellbeing

Abstract: A qualitative study using group and individual interviews involving 10 veterinary hospitals in Wellington County, Ontario, explored how the practices involved in euthanasia-related care impacts the wellbeing of veterinary professionals. Thematic analysis indicated two major outcomes: the goal and desire of veterinary professionals was to facilitate a 'good death' for the companion animal and navigating the euthanasia decision process was more challenging than the actual event of performing euthanasia. When suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 38 publications
0
46
0
4
Order By: Relevance
“…Risk factors among veterinarians, such as suicidal ideation, attempts at one’s own life, and depression, have been cited in the literature, both in the U.S. and in other countries [ 29 , 30 , 31 , 32 , 33 ]. Other challenges facing the veterinary health profession are well documented within the industry, including student debt loads [ 34 ], mental health implications arising from compassion fatigue [ 35 ], and the impact of performing euthanasia [ 36 ], in addition to lesser discussed but more obvious risks to (human) physical safety arising from working with animals [ 37 ]. While these challenges and issues are being raised in the media and in the literature around the world, veterinary suicides were not found in the searches conducted in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors among veterinarians, such as suicidal ideation, attempts at one’s own life, and depression, have been cited in the literature, both in the U.S. and in other countries [ 29 , 30 , 31 , 32 , 33 ]. Other challenges facing the veterinary health profession are well documented within the industry, including student debt loads [ 34 ], mental health implications arising from compassion fatigue [ 35 ], and the impact of performing euthanasia [ 36 ], in addition to lesser discussed but more obvious risks to (human) physical safety arising from working with animals [ 37 ]. While these challenges and issues are being raised in the media and in the literature around the world, veterinary suicides were not found in the searches conducted in this study.…”
Section: Discussionmentioning
confidence: 99%
“…They also describe vets' reduced sense of wellbeing and emotional strain when discussions around euthanasia are prolonged or complicated, thus making the euthanasia decision-making consultations more diicult and distressing than the act of euthanasia itself. 10 Vets are reported to be present during the death of their patients ive times more oten than general practitioners in human healthcare. 11,12 Animals will present on the brink of death and requiring euthanasia through trauma, illness, injury, abuse and human abandonment.…”
Section: Animal Euthanasia -Empathic Care or Empathic Distress?mentioning
confidence: 99%
“…Drawing a distinction between the act of euthanasia and the process of euthanasia, as suggested by Matt and colleagues, 10 provides an important insight into developing strategies to support veterinary professionals. Vets are already at risk of higher levels of stress linked to depressive symptomology due to occupational…”
Section: What You Need To Knowmentioning
confidence: 99%
See 1 more Smart Citation
“…We encourage readers to also consider reading the article by Matte and others, 1 who found that when veterinary professionals successfully navigate euthanasia decisions and help shepherd pets through a ‘good death’, their sense of wellbeing, and that of their clients, improves.…”
mentioning
confidence: 99%